Accounting Information Systems: A Control Emphasis (Book). - Hendrickson, Harvey S.; Siebel, Jerry D. (The Accounting Review, 1985)
Abstract Reviews the book "Accounting Information Systems: A Control Emphasis," by David H. Li.